Pengaruh Kinerja Lingkungan Dan Kinerja Keuangan Teradap Pengungkapan Informasi Lingkungan - Nur Chanifah (WIDYAKALA: JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2019)
This research is using quantitive study aimed to see whether there are influence of environmental performance and financial performance on environmental disclosure. This study uses non-financial companies listed on the Indonesia Stock Exchange as a population. Sample selected by purposive sampling and collected 20 non-financial companies, with a research period of 2015-2017, but for the measurement of financial performance, the data taken was data for 2014-2016, because in this study, tested is the effect of financial performance in the previous year on disclosure of environmental information in the current year. Testing the hypothesis in this study uses Multiple Linear Regression Analysis with SPSS version 25 and a significance level of 5% (0.05). The results of this study indicate that: (1) environmental performance has a significant positive effect on environmental disclosure, (2) financial performance in the previous year has a significant negative effect on environmental disclosure in the current year. The variables of environmental performance and financial performance can explain the environmental disclosure variable of 26,4%.Keywords : Environmental Disclosure, Environmental Performance, Financial Performance